Fabrication of anti-icing/de-icing surfaces by femtosecond laser - Tang, Bo-Hao; Wang, Qiang; Han, Xing-Chen; Zhou, Hao; Yan, Xiao-Jing; Yu, Yi; Han, Dong-Dong (Frontiers in Chemistry, 2022)
In this minireview, we comprehensively reviewed recent progress on fabricating anti-icing/de-icing surfaces by femtosecond laser technologies. Typical bioinspired micro-/nano-structures fabrication strategies, superhydrophobic surfaces with anti-icing properties, and photothermal surfaces with de-icing properties are summarized. At last, we discussed challenges and prospects in anti-icing/de-icing surfaces fabricated by femtosecond laser technologies.